The influence of entrepreneurship in planning an internationalization strategy - Fonseca, João Francisco Pina (2020)
Since the beginning of the 21st century, there has been a change in culture and, consequently, a change in the way of thinking and living, today people have stopped focusing only on the border areas of their country to start looking for opportunities outside their own country. comfort zones. With this new way of looking at the world, a strong technological advance was added, these variables contributed to the existence of a much more dynamic and competitive market. From this competitiveness arises the need for companies to open their field of vision looking for new alternatives and new opportunities, and if they do not intend to survive, they cannot limit themselves to the competitive advantages they have, under penalty of “losing the train” of entrepreneurship. The elaboration of a strategic plan, therefore, presents itself as a mandatory step to respond to the needs of a company. In a completely globalized world, where physical boundaries are no longer a barrier, the main objective of this investigation is to find out whether current leaders are preparing to compete in the current world market and how they put all these changes in their favor. On the other hand, more and more leaders believe it is possible to make business decisions, while simultaneously increasing revenues and managing positive economic and social results in the communities where they operate, as there are a range of alternatives and business options. Another objective of this dissertation is precisely to find out how Portuguese leaders face these new opportunities, and resort to the implementation of innovative strategies in order to increase their business performance, achieve their strategic objectives, and compete with companies worldwide. In this sense, several interviews were conducted with sixteen leaders in our country, from companies under ten years old, in order to understand their perception of the current market situation, in order to understand the consequences of competing at a global level, and in parallel if they are willing to search for new alternatives to update, materialize and boost their commercial activity. It is conclusive that although leaders recognize the need for good planning to be competitive internationally, the dynamism of the current market, leads leaders to devote less time and resources to this task. The speed and ease of creating business, has led companies to think more and more in the short term, and entrepreneurs who are not afraid to start, have become more important not only for companies but for society in general.